Inteligências múltiplas de Gardner: É possível pensar a inteligência sem um factor g? - Almeida, Leandro S. (2009)
As an answer to the reviews stating the lack of innovation in test methodology as well as the little attention given to the social and cultural variables in intelligence assessment, Gardner (1983, 1999) develops the Multiple Intelligence (MI) theory with more ecological tasks which are closer to the subjects’ daily routines so that these may be evaluated. In the Spectrum Project framework, several tasks were developed to measure MI, 6 of which were chosen and measure specific intelligences, namely, verbal-linguistic, corporal-kinesthetic, visual-spatial and musical, mathematics. A total of 294 children aged 5 to 7 were evaluated on those tasks. Results show that if at a precision level, the internal consistence indices may be considered reasonable, than there must be some concerns in regards to the construct validity in Gardner’s theoretical model. In fact, and contrarily to Gardner’s position, it is possible to find a general factor, despite not measuring more than 40% of the explained variance. Evidence was not found concerning factors that could group some of these intelligences, as recently proposed by Gardner.